2000
DOI: 10.1007/bf03173173
|View full text |Cite
|
Sign up to set email alerts
|

How the socioecological characteristics of the classroom affect academic achievement

Abstract: The aim of this study was to grasp and understand the socialpsychological mechanisms by which the classroom socioecological environment determines academic achievement. Wefirst developed and tested a general theoretical model (on a sample of 51 classrooms containing 1123junior high school students) which allows us to consider the classroom social climate as a dependent and independent variable. We then attempted to accurately define the influence mechanism and develop a structural model to account for the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
(30 reference statements)
1
3
0
6
Order By: Relevance
“…The problems shown by this subgroup relate mainly to school motivation and a lack of interest in school; however, they establish good relationships with their teachers. In keeping with this finding, Bennacer (2000) shows that school achievement is associated with classroom organization and a strong focus on the task. Further, Janosz and LeBlanc (1996) report that the dropout risk increases when a school is unable to provide a clear, consistent and wellstructured framework.…”
Section: School Dropout Risk Typology: Four Specific Profiles On Famisupporting
confidence: 66%
See 1 more Smart Citation
“…The problems shown by this subgroup relate mainly to school motivation and a lack of interest in school; however, they establish good relationships with their teachers. In keeping with this finding, Bennacer (2000) shows that school achievement is associated with classroom organization and a strong focus on the task. Further, Janosz and LeBlanc (1996) report that the dropout risk increases when a school is unable to provide a clear, consistent and wellstructured framework.…”
Section: School Dropout Risk Typology: Four Specific Profiles On Famisupporting
confidence: 66%
“…Pierce (1994) found that the classroom climate and the interactions between teacher and student had an effect both on academic achievement and the student's engagement in school and social activities. In a study of 1,123 high school students, Bennacer (2000) reported that the teacher could foster academic achievement by improving the psychosocial conditions in the classroom. For example, classroom organization and task orientation stimulated better academic performance.…”
Section: School Factors Associated With Dropout Riskmentioning
confidence: 99%
“…Aussi, Pierce (1994) estime que le climat de classe et les interactions entre l'enseignant et l'élève ont un effet, d'une part, sur la réussite scolaire et, d'autre part, au plan de l'engagement du jeune dans ses activités scolaires et sociales. Dans une étude menée auprès de 1 123 élèves du secondaire, Bennacer (2000) rapporte que l'enseignant peut favoriser la réussite scolaire en développant de meilleures conditions psychosociales en classe. Par exemple, l'organisation de la classe et l'orientation vers la tâche favorisent une meilleure performance scolaire.…”
Section: Facteurs Scolaires Associés Au Décrochage Scolaireunclassified
“…B. Lernstrategien, kooperatives Lernen). Insgesamt berichten 80 internationale publikationen mit 134 nennungen über Kriterien für die wirksamkeit von Unterrichtsmerkmalen und -prozessen (Alexander et al 2002;Allsopp 1997;Anderman et al 2001;Applebee et al 2003;Arnold et al 2002;Ashman/Gillies 1997;Baumann et al 2003;Behets 2001;Bennacer 2000;Bianchini 1997;Borsch/Jurgen-Lohmann/Giesen 2002;Brush 1997;Byrne/Fieldingbarnsley 1995;cantrell 1999;chang 2002;chang/Barufaldi 1999;chinn/Anderson/waggoner 2001;chularut/DeBacker 2004;cooper et al 1998;crinjen/Feehan 1998;D'Agostino 2000;De Fraine et al 2003;De Jong/westerhof/Kruiter 2004;Driessen/Sleegers 2000;Einsiedler/Treinies 1997;Foorman et al 1998;Freedman 1997;Fuchs et al 1997;George/ Kaplan 1998;Ginsburg-Block/Fantuzzo 1998;Gruehn 1995;Guthrie et al 1998;Hamilton et al 1995;Hardre/Reeve 2003;Henderson/Landesman 1995;Hogan 1999;Hopkins/McGillicuddy-DeLisi/DeLisi 1997;Houghton/Litwin/carroll 1995;Houtveen et al 1999;Jacobson/Lehrer 2000;…”
Section: Effektivitätskriterien Auf Der Ebene Von Merkmalen Und Prozeunclassified